Pemanfaatan Dana Zakat Bagi Pembaerdayaan Ekonomi Umat (Analisis Fatwa Mui Tahun 1982) - Said Ahmad Sarhan Lubis (AGHNIYA : Jurnal Ekonomi Islam, 2019)
Zakat is an interesting topic to study. There has been a lot of literature that tries to lookat zakat from various systems such as from legal aspects or fiqh, management, potential,and its role in eradicating poverty. The obligation of zakat in Islam has a veryfundamental meaning. Apart from being related to divine aspects as well as economicand social aspects. The fatwa commission of the Indonesian Ulama Council in 1982issued a fatwa concerning the Utilization / Management (Tasharruff) of Zakat Funds forProductive and Public Prosperity Activities. From the aspect of social justice or (alalahadalahal-ijtimai'yyah), the command of zakat can be understood as an inseparableunitary system in achieving socio-economic and social welfare. Zakat is expected tominimize the income gap between the rich and the poor. In addition, zakat is alsoexpected to increase or grow the economy both at the individual level and at the sociallevel. But unfortunately, the obligation of zakat is still rarely proven by economic logic(fiscal policy).